Indonesian language training and introduction of Al-Islam Kemuhammadiyahan (AIK) to the Thai muslim community - Nur Rizqi Febriandika; Harun Harun; Sausan Liski Aulia; Alif Rio Harsenda; Wildan Hamdani; Syamsul Hidayat (Community Empowerment, 2023)
Thailand is a country in Southeast Asia and is in the form of a unitary state with a majority population of Buddhist beliefs. However, in Southern Thailand, the majority are Muslims with Malay cultural features and there are many Islamic-based educational institutions. It is not uncommon for the people of Southern Thailand to send their children to study in Indonesia. One of the problems faced is the small number of Muslim people who can speak Indonesian. Therefore, we conducted a 1-month training in the context of providing language training and Al-Islam Kemuhammadiyahan (AIK) to the Thai Muslim community in collaboration with the Association of Education Cultural International (AECI). The results of the activity showed that the students' understanding of Indonesian grammar at Eakkapapsassanawich Islamic School and Adameesuksavittaya School increased significantly. Likewise with understanding related to Al-Islam Kemuhammadiyahan.